Renaissance Rewritings - Fantappiè, Irene; Pfeiffer, Helmut; Roth, Tobias 1985- (Transformationen der Antike, 2017)
‘Rewriting’ is one of the most crucial but at the same time one of the most elusive concepts of literary scholarship. In order to contribute to a further reassessment of such a notion, this volume investigates a wide range of medieval and early modern literary transformations, especially focusing on texts (and contexts) of Italian and French Renaissance literature. The first section of the book, "Rewriting", gathers essays which examine medieval and early modern rewritings while also pointing out the theoretical implications raised by such texts. The second part, "Rewritings in Early Modern Literature", collects contributions which account for different practices of rewriting in the Italian and French Renaissance, for instance by analysing dynamics of repetition and duplication, verbatim reproduction and free reworking, textual production and authorial self-fashioning, alterity and identity, replication and multiplication. The volume strives at shedding light on the complexity of the relationship between early modern and ancient literature, perfectly summed up in the motto written by Pietro Aretino in a letter to his friend the painter Giulio Romano in 1542: "Essere modernamente antichi e anticamente moderni"